Integrated knowledge translation (iKT) in preclinical research: A scoping review protocol - Georgia Black; Reena Besa; Daniel Blumberger; Heather Brooks; Graham Collingridge; John Georgiou; Evelyn K. Lambe; Clement Ma; Bernadette Mdawar; Tarek K. Rajji; Sanjeev Sockalingam; Cara Sullivan; et al. (PLoS ONE, 2025)
Introduction Integrated knowledge translation (iKT) is a collaborative research approach that emphasizes the meaningful and active participation of knowledge users throughout the research process. Evidence suggests that integrated knowledge translation has the potential to increase the relevance, applicability, and use of research findings. This approach has been increasingly utilized in health research in recent years. However, the extent to which it has been applied in preclinical research and its effectiveness are unknown. To address this gap, we will conduct a scoping review to map the current use, potential benefits, and challenges of iKT in preclinical research. Methods Guided by a modified Arksey and O’Malley’s scoping review framework, we will systematically search reference lists and key research databases including Medline, Embase, PsycINFO, Cochrane CENTRAL, Cochrane Database of Systematic Reviews, and Web of Science. Peer-reviewed articles written or translated in English that focus on iKT or approaches that align with iKT within the context of preclinical research will be included. This review will be conducted as part of the I mproving N europlasticity through S paced P refrontal i ntermittent-Theta-Beta-Stimulation RE finement in D epression ( INSPiRE-D) project, which features preclinical research from mouse models to human work (Grant number CAMH File No.22-060). The project’s multidisciplinary team and knowledge user advisory committee will be consulted at key points throughout the scoping review process. A person with lived experience co-chairs the project advisory committee, co-authored this manuscript, and will be routinely included in the decision-making process of the scoping review.